Neem - a Green Contraceptive - Kumar, Shashi; Jattan, S. S. (Indian Forester, 1995)
Having multifarious medicinal properties Neem "A Wonder Tree" is found to be a potent contraceptive. Its efficacy as anti-fertility agent has been tested on rats and bonnet monkeys. With little more research on Neem oils chemical aspects, derivatives and mechanisms of action it will be a proven wonder drug which can be patented for human being as an alternate approach to vasectomy and Intra Uterine Contraceptive Device (IUCD). The tree will prove to be a major source of income/ revenue capturing the market in India and abroad.